SOCIAL CONSTRUCTION FANDOM AS CULTURAL INDUSTRY MARKETING: CASE STUDY OF JKT 48 FAN GROUP - Mulyana, Ahmad; Briandana, Rizki; Ningrum, Dwi Anggraini Puspa (Universitas Prasetiya Mulya, 2019)
Not a few people who have a deep interest in a cultural product such as music, then identify themselves as a fan. This reality is one of the popular culture products which is quite popular with a group of JKT 48 fans. This study uses a case study method with the aim of analyzing the social construction of marketing of the JKT48 fandom group in the context of the cultural industry context. The results show that the social construction of fandom is formed on the same interest in a cultural form. The presence of JKT48 in the study of pop music culture gives a new color in forming a subculture about the concept of how to become a fan as well as a consumer of popular culture. This relates to the marketing of culture as a form of the cultural industry as a contribution to cultural production.